COVID-19, deforestation, and green economy - Singhal, Vibha; Jinger, Dinesh; Rathore, Avinash Chandra; Pal, Rama; Samal, Ipsita; Bhoi, Tanmaya Kumar; Paramesh, Venkatesh; Fahad, Shah; Jaremko, Lukasz; Abdelsalam, Nader R.; Jaremko, Mariusz (Frontiers in Forests and Global Change, 2024)
Corona has severally impacted many sectors past two and half years, forests are one of the major hits among all sector affected by the pandemic. This paper presents the consolidated data on deforestation pattern across the globe during covid and also analyzed in depth the region-specific contributing factors. Exacerbated deforestation during covid alarms the biodiversity conservation concerns and pushes back the long-term efforts to combat pollution and climate change mitigation. Deforestation also increases the risk of emergence of new zoonotic diseases in future as deforestation and covid are intricately related to each other. Therefore, there is need to check deforestation and inculcation of conservation measures in building back better policies adopted post covid. This review is novel in specifically providing insight into implications of COVID-19 on forests in tropical as well as temperate global regions, causal factors, green policies given by different nations and recommendations which will help in designing nature based recovery strategies for combating deforestation and augmenting afforestation thus providing better livelihood, biodiversity conservation, climate change mitigation and better environmental quality.